Ultra-thin GaAs double-junction solar cell with carbon-doped emitter - Ren, Zekun; Thway, Maung; Liu, Zhe; Wang, Yue; Ke, Cangming; Yaung, Kevin N.; Wang, Bing; Tan, Chuan Seng; Lin, Fen; Aberle, Armin G.; Buonassisi, Tonio; Peters, Ian Marius (IEEE Journal of Photovoltaics, 2018)
We address the challenge in depositing ultra-thin GaAs cells (<200 nm) using a more scalable process (metal-organic chemical vapor deposition). We present results for a GaAs/GaAs double-junction solar cell with a 110-nm-thick top cell. Current, voltage, fill factor, and efficiency of this architecture are improved by replacing the zinc doping in the emitter of the top cell with carbon doping. We find that the carbon doping results in a well-defined active junction profile that agrees well with the secondary ion mass spectroscopy measurement. Additionally, we find that the carbon doping coincides with the incorporation of indium in the emitter. We postulate that the incorporation of indium relieves stress in the material, which results in a smoother morphology of the GaAs film. Finally, we show the efficiency achieved with the carbon-doping process is 19.2% for the GaAs/GaAs dual junction cell. The open circuit voltage is 1.087 V for the ultra-thin (110 nm) GaAs top cell and 2.08 V for the dual junction cell.
CRIS-Team Scopus Importer:2022-06-05
Keywords: III-V on Si; III-V tandem; One sun tandem solar cell; ultra-thin GaAs